Mathematical modeling of optical and thermal behaviour of a new cascade nanofluid-based PV/T system / Samir Hassani - Samir, Hassani (2017)
In the last few decades, scientists and engineers have increasingly focused on maximizing the efficiency of solar-harvesting technologies. Photovoltaic/thermal (PV/T) solar systems, which produce both electrical and thermal energy simultaneously, represent a method to achieve very high conversion rates of sunlight into useful energy. In recent years, nanofluids have been proposed as efficient coolant fluids and as a means to filter sunlight for PV/T systems. In the present study, a new architecture of nanofluid-based PV/T hybrid system with separate channels is proposed, where one channel controls the optical properties while the other enhances heat removal from the PV cells. That is, the first nanofluid, optical nanofluid, acts as a liquid optical bandpass filter above the PV cells while the second, thermal nanofluid, removes heat from the back of the PV cells. The proposed PV/T system was simulated for both GaAs and Si-based PV cells at various solar concentration ratios, and its electrical and thermal performance were determined numerically using advanced modeling and simulation approaches. Nanofluids’ thermal conductivities were optimized using a new correlation for predicting the thermal conductivity of nanofluids developed herein. The correlation has been developed using Vaschy-Buckingham theorem and derived from 196 values of nanofluids thermal conductivity, 86% of them are correlated within a mean deviation of ±5%, while 98% of them belong to an interval of ±10%. An improved algorithm for Mie theory was developed to measure nanofluid optical properties. In addition, a modified electrical model was established to predict electrical efficiency of Si and GaAs cells. To verify the design performance of the proposed nanofluid-based PV/T system with separate channels (D-1), a comparative analysis, in terms of electrical and thermal output, is conducted between the latter and a nanofluid-based PV/T with double-pass channel (D-2). In concentrated solar systems, it was found that the separate channel system (D-1) outperformed the double-pass design (D-2) by ~8.6%, in terms of the electrical efficiency of GaAs and Si. The overall efficiency of the D-1 system with GaAs and Si have been improved by ~5.8% and ~4.6%, respectively, by increasing the volume fraction of the thermal nanofluid. Generally, it was found that the proposed PV/T configuration with separate channels has potential for further development in high-concentration (C >100) solar systems. In order to assess the environmental and exergy life cycle of the proposed PV/T system D-1, another comparative analysis has been conducted between the system D-1, standard PV panel and conventional PV/T system. The life cycle exergy analysis revealed that system D-1 showed the best performance compared to a standard PV and PV/T systems. In instance, the system D-1 produces ~1.3